From Song to Visual Art: Exploring Sehnsucht in the lived experiences of visual artists - Conroy A. Cupido (The Journal for Transdisciplinary Research in Southern Africa, 2016)
This article explored the experiences shared by four artists during their processes of creating an art work which represented a specific art song or Lied. During 2015, South African artists Marna de Wet, Kevin du Plessis, Jean Lampen and Eljana van der Merwe collaborated with the pianist Tinus Botha and baritone Conroy Cupido. The essence of the poetry and music of Vaughan Williams, Quilter, Schumann, Strauss and Brahms presented in this project conveyed a feeling known as Sehnsucht. The purpose of this article was to understand the experiences of these artists during their creative processes. Their processes entailed ascribing meaning and communicating their interpretation of the elements of Sehnsucht from the music and poetry to visual art. This was achieved through interpretative phenomenological analysis. The artists used various media including, charcoal on paper, oil paint on sourced objects, oil on canvas and photography to portray their interpretations. Through their artistic processes, the artists uncovered melancholy, Wanderlust, homo-eroticism, longing and the desire for love in the music and poetry. One of the artists discovered how her own concept of idealised love had evolved through her artistic process. The artists used both music and narrative content to visualise Sehnsucht; however, due to the non-referential nature of music, the artists were not always able to verbalise how the music influenced their work. The article includes images of some of the art works.